Analisis Angka Mortalitas pada Tahun 2023 Sampai Triwulan Pertama Tahun 2024 Berdasarkan Indikator Gross Death Rate (GDR) dan Net Death Rate (NDR) di Rumah Sakit X - Iis Rostika; Ade Irma Suryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the mortality rates for both the gross and net deaths, data sources, and statistical activities from 2023 to the first quarter of 2024 at X Hospital. Combining evaluation studies—that is, qualitative and quantitative—with a descriptive research methodology. The data processing techniques are interviewing and observation. The qualitative data is processed using an inductive approach, and the quantitative data is processed using bivariate analysis. The population is the research informant, consisting of 5 officers, and the object is the Monthly Recapitulation Form of Hospitalized Patients. The study's results show that the Republic of Indonesia's (Depkes RI) Ministry of Health has set standards for Gross Death Rate <45% and Net Death Rate <25%. The study's results show that the Gross Death Rate value in 2023 is 21.02%, while the Net Death Rate value is 7.15%. The study concludes that the data source obtained is the result of a monthly recapitulation of hospitalized patients with statistical activities in reporting data processing according to the formula used for calculating the Gross Death Rate and Net Death Rate values and the data is presented in Microsoft Excel as tables and graphs.